Comparison of Combined Nebulization of Salbutamol-Ipratropium Bromide with Salbutamol Alone in Children with Mild and Moderate Acute Asthma - Mujahid Hussain , Mahnoor, Mujahid Hussain , Mahnoor (Journal of Rawalpindi Medical College, 2020)
ntroduction: The β2 agonists are potent bronchodilators but their repeated and high doses are related to adrenergic side effects. While ipratropium bromide, an anticholinergic bronchodilator has less adverse effects. Objective: To compare the efficacy of combined nebulization of salbutamol-ipratropium bromide with salbutamol alone in children with mild and moderate acute asthma. Materials and Methods: This randomised control trial was done on 80 children aged 5 to 12 years who presented with mild to moderate acute asthma in the emergency department of Children Hospital of Pakistan Institute of Medical Sciences (PIMS) from July 2014 to June 2016 and randomized into 2 groups. In the experimental group each child received 2 nebulizations of combined salbutamol (5mg) and ipratropium Bromide (0.25mg) at presentation and 20 minutes later. Similarly, each child of the control group received 2 nebulizations of 5mg Salbutamol and 2 ml of Normal saline. Asthma clinical score (ACS) was assessed at baseline and then after every 20 minutes up to one hour after the presentation. Results: In the experimental group, the mean + SD ACS at presentation and 60 minutes were 3.50±1.8 and 3.45±1.7 respectively with mean + SD change in ACS of 0.05 ± 0.1. In the control group, the mean + SD ACS at presentation and 60 minutes were 3.70 ± 1.2 and 3.60 ± 1.9, respectively with mean + SD change in ACS of 0.1 ± 0.7. This difference in mean + SD change in ACS between 2 groups was not statistically significant (P=0.6560). Conclusion: There is no statistically significant benefit of adding ipratropium bromide with salbutamol nebulization as compared to salbutamol alone for the management of children with mild to moderate asthma attacks.